Developing Leadership Theories in Environment Remote Work - Halim , Stievan K.; Hendayana , Yayan (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Review literature This to study theory evolving management​ in leadership organization between 2020 and 2024 which handles challenge environment Work distance distant and hybrid . Through analysis systematic to work scientific latest , review This identify three approach the key that marks a real shift from the leadership model traditional : digital competence , communication adaptive , and retrieval decision together . Findings This show that leadership in environment Work distance far and hybrid need different competencies and approaches​ compared to with paradigm leadership traditional , especially For manage team distributed in a way effective .